1998
DOI: 10.1073/pnas.95.23.13419
|View full text |Cite
|
Sign up to set email alerts
|

An autonomous folding unit mediates the assembly of two-stranded coiled coils

Abstract: Subunit oligomerization of many proteins is mediated by coiled-coil domains. Although the basic features contributing to the thermodynamic stability of coiled coils are well understood, the mechanistic details of their assembly have not yet been dissected. Here we report a 13-residue sequence pattern that occurs with limited sequence variations in many two-stranded coiled coils and that is absolutely required for the assembly of the Dictyostelium discoideum actin-bundling protein cortexillin I and the yeast tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
176
1
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(193 citation statements)
references
References 40 publications
15
176
1
1
Order By: Relevance
“…Characterization of small peptides and larger recombinant regions demonstrates that trigger sequences possess the ability to form α-helices, and these helices, once formed, are hypothesized to lead to the zipping up of the entire coiled-coil (41). Although the name implies that these regions trigger coiled-coil formation, the order of assembly within IFs has not been demonstrated (39,41). An examination of IF sequences for trigger sequences has resulted in the identification of two regions with sequence similarity and, more importantly, functional requirements for coiled-coil formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Characterization of small peptides and larger recombinant regions demonstrates that trigger sequences possess the ability to form α-helices, and these helices, once formed, are hypothesized to lead to the zipping up of the entire coiled-coil (41). Although the name implies that these regions trigger coiled-coil formation, the order of assembly within IFs has not been demonstrated (39,41). An examination of IF sequences for trigger sequences has resulted in the identification of two regions with sequence similarity and, more importantly, functional requirements for coiled-coil formation.…”
Section: Discussionmentioning
confidence: 99%
“…These locations flank the early assembling region we have identified within linker 2. Assuming a conservation of structural elements between type I and II keratins and type III vimentin, the action of linker 2 as an early assembly facilitator could easily be incorporated into the model by Kammerer as an interaction that brings two polypeptide chains together and, thus, facilitates the transition from two autonomous helical folding units to a parallel in-register alignment of two monomers (step i to ii of the model of Kammerer et al (41).…”
Section: Discussionmentioning
confidence: 99%
“…Collision of short helical-like stretches has been suggested as a mechanism for the folding pathways of GCN4p1 (46,47). As a local factor, Gazit (35) has suggested that aromatic residues can provide two key elements for the formation of such structures: (i) an energetic contribution stemming from the -stacking itself; and (ii) specific directionality and orientation provided by the specific pattern of stacking.…”
Section: Discussionmentioning
confidence: 99%
“…Because the presence of such an inducer can propagate coiled-coil formation over long distances (10), and because regulation in smooth-muscle myosin II requires the presence of at least 15 heptads (4), the chimeric S2N51 construct may not reveal important structural and functional features of S2. To gain further insight into the S2 region, and because of its clinical importance, we have determined crystal structures of the native N-terminal 126 residues of S2 from human cardiac ␤-myosin II (S2-⌬, P838-K963, covering Ϸ30% of the complete S2 subfragment) and its FHC-associated mutant E924K to 2.7-and 2.5-Å resolution, respectively.…”
mentioning
confidence: 99%